Analysis of design principles and requirements for procedural rigging of bipeds and quadrupeds characters with custom manipulators for animation - Bhati, Zeeshan; Shah, Asadullah; Waqas, Ahmad; Mahmood, Nadeem (AIRCC Publishing Corporation, 2015)
Character rigging is a process of endowing a character with a set of custom manipulators and controls making it easy to animate by an animators. These controls consists of simple joints, handles, or even separate character selection window. This research paper presents an automated rigging system for quadruped characters with custom controls and manipulators for animation. The full character rigging mechanism is procedurally driven based on various principles and requirements used by the riggers and animators. The automation is achieved initially by creating widgets according to the character type. These widgets then can be customized by the rigger according to the character shape, height and proportion. Then joint locations for each body parts are calculated and widgets are replaced programmatically. Finally a complete and fully operational procedurally generated character control rig is created and attached with the underlying skeletal joints. The functionality and feasibility of the rig was analyzed from various sources of actual character motion and a requirements criterion was met. The final rigged character provides an efficient and easy to manipulate control rig with no lagging and at high frame rate.